Utilising Instagram as a Promotional Medium for Car Rental at Anugrah Rent Car Medan - Juprijal Raman Rambe (Indonesian Journal of Communication and Social, 2025)
This study analyzes the use of Instagram as a promotional medium in the car rental business at CV Anugrah Rent Car Medan. The background of this research is driven by the increasing use of social media as a marketing tool, including in the car rental service industry. The main focus of the study is to identify and understand how CV Anugrah Rent Car Medan utilizes Instagram features to promote its services. The research method employed is descriptive qualitative, with data collected through direct interviews with relevant parties at CV Anugrah Rent Car Medan. Data analysis was conducted by describing the findings from the interviews and linking them to concepts of digital marketing. The results indicate that CV Anugrah Rent Car Medan has successfully leveraged Instagram effectively as a promotional medium. The utilization of this platform includes the use of photos, feeds, stories, status updates, viewers, and hashtags to broaden the reach of its car rental service promotions. By maximizing the available features on Instagram, CV Anugrah Rent Car Medan has been able to enhance the visibility and attractiveness of its services in the market. In conclusion, the descriptive qualitative approach provides an in-depth understanding of the dynamics of Instagram utilization as a marketing tool for car rental services. This study implies that marketing strategies through social media, particularly Instagram, can serve as an effective solution to strengthen promotion and increase sales in the car rental service industry.